2014
DOI: 10.1371/journal.ppat.1004518
|View full text |Cite
|
Sign up to set email alerts
|

Retromer Regulates HIV-1 Envelope Glycoprotein Trafficking and Incorporation into Virions

Abstract: The envelope glycoprotein (Env) of the Human Immunodeficiency Virus Type-1 (HIV-1) is a critical determinant of viral infectivity, tropism and is the main target for humoral immunity; however, little is known about the cellular machinery that directs Env trafficking and its incorporation into nascent virions. Here we identify the mammalian retromer complex as a novel and important cellular factor regulating Env trafficking. Retromer mediates endosomal sorting and is most closely associated with endosome-to-Gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 60 publications
0
76
0
Order By: Relevance
“…Using PGT151, we were able to isolate a component of pseudovirion Env that had a range of complex-type sugars similar to that isolated from PBMC-derived Env, except for a different linkage of terminal sialic acids. These highly processed complex-type glycans might be indicative of a prolonged exposure in the Golgi or retromer-mediated sorting of virion-associated Env from the cell surface back to the Golgi, as has recently been demonstrated (64). In contrast, recombinant gp120, which is not membrane bound, displayed an additional range of smaller complex-type glycans, suggesting faster transit through the Golgi apparatus.…”
Section: Figmentioning
confidence: 56%
“…Using PGT151, we were able to isolate a component of pseudovirion Env that had a range of complex-type sugars similar to that isolated from PBMC-derived Env, except for a different linkage of terminal sialic acids. These highly processed complex-type glycans might be indicative of a prolonged exposure in the Golgi or retromer-mediated sorting of virion-associated Env from the cell surface back to the Golgi, as has recently been demonstrated (64). In contrast, recombinant gp120, which is not membrane bound, displayed an additional range of smaller complex-type glycans, suggesting faster transit through the Golgi apparatus.…”
Section: Figmentioning
confidence: 56%
“…Mutations in these putative protein-binding sites were found to exhibit reduced cell-free infectivity, which was cell type dependent in the case of the prohibitin binding site mutant LL_RQ. The cellular retromer complex has also recently been shown to bind to the CT (21). Disruption of retromer-CT interaction can result in the production of virus particles with enhanced Env packaging and infectivity.…”
mentioning
confidence: 99%
“…A number of studies have examined HIV-1 genomes carrying progressive gp41 CT truncations and observed differential impacts on Env fusogenicity (1,3,26), Env packaging, and/or infectivity of cell-free virus (3,(26)(27)(28)(29)(30)(31). Other studies have also characterized small deletions and point mutations within the CT LLP regions or endocytic motif(s) that affect Env incorporation and/or infectivity of viral particles (2,6,(31)(32)(33)(34)(35), the intracellular distribution of Env (21,33), syncytium formation (2,6,34), viral fusion (6,35), and polarized budding (36).…”
mentioning
confidence: 99%
“…Human immunodeficiency virus (HIV-1) has been shown to use retromer-based recycling in the process of virion construction (Fig. 3A), specifically involving the two component envelope (Env) proteins (gp120 and gp41) (Blot et al, 2003;Groppelli et al, 2014). Not only do retromer proteins show intracellular colocalization with HIV-1 particles in vivo, but retromer proteins Vps26 and Vps35 have been shown to physically interact directly with the Table 1 Examples of mammalian retromer cargo proteins.…”
Section: Viral Pathogensmentioning
confidence: 99%